Combined immunosuppressive therapy provides favorable prognosis and increased risk of cytomegalovirus reactivation in anti‐melanoma differentiation‐associated gene 5 antibody‐positive dermatomyositis. Issue 5 (24th February 2020) - Matsuda, Kazuki M.; Yoshizaki, Ayumi; Kuzumi, Ai; Fukasawa, Takemichi; Ebata, Satoshi; Yoshizaki‐Ogawa, Asako; Sato, Shinichi
Abstract: Anti‐melanoma differentiation‐associated gene 5 (MDA5) antibody (Ab) is myositis‐specific autoantibody associated with rapidly progressive interstitial lung disease (ILD) and poor prognosis. In this retrospective observational study, we aimed to verify the efficacy and safety of introducing combined immunosuppressive therapy for anti‐MDA5 Ab‐positive dermatomyositis (DM) from their early stage. We recruited all Japanese patients diagnosed with DM in our clinic between January 2011 and October 2018, who had anti‐MDA5 Ab, anti‐aminoacyl transfer RNA synthetase Ab or anti‐transcriptional intermediary factor 1‐γ Ab. Combined immunosuppressive therapy was defined as combination of systemic corticosteroids, i.v. cyclophosphamide and tacrolimus. The difference of clinical features among the three groups was analyzed by multiple comparison analysis. The longitudinal change of the measurements from baseline was examined by Wilcoxon signed‐rank test. Association between therapeutic regimens and adverse events was examined by logistic regression analysis. As a result, combined immunosuppressive therapy was most frequently used in the anti‐MDA5 Ab‐positive group, which significantly improved their forced vital capacity of the lung. Interval time since initial visit until starting treatment was the shortest in the anti‐MDA5 Ab‐positive group. There was no significant difference in the incidence of death and recurrence among the three groups. Cytomegalovirus reactivation was most common in the anti‐MDA5 Ab‐positive group, associated with combined immunosuppressive therapy. Collectively, early introduction of combined immunosuppressive therapy was effective for DM patients with anti‐MDA5 Ab. At the same time, clinicians should be aware of the risk of cytomegalovirus reactivation during the treatment.